Protective effect of melatonin against methotrexate-induced testicular damage in the rat model: An experimental study - Wannisa Sukhorum; Jariya Umka Welbat; Suchada Krutsri; Sitthichai Iamsaard1comma (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Methotrexate (MTX) has been shown to affect the testes adversely, especially the seminiferous epithelium. As melatonin, an endocrine hormone, has been shown to normalize testicular function, its ability to prevent MTX-induced testicular damage should be considered. Objective: Based on the antioxidant, anti-inflammatory, and antiapoptotic activities of melatonin, this study aimed to investigate its protective effect against testicular damage induced by MTX. Materials and Methods: Forty adult male rats (200-230 g) were divided into five groups (n = 8/each). The rats in group I were injected with vehicle as a control. In group II, the rats were received intraperitoneal injections of melatonin (8 mg/kg) for 15 consecutive days. The rats in group III were intravenously injected with MTX (75 mg/kg) for 15 consecutive days. The remaining two groups received melatonin (8 mg/kgBW) for 15 (group IV) and 30 (group V) consecutive days, intraperitoneally, and then intravenously received MTX (75 mg/kgBW) on days 8 and 15 of the experimental period. Reproductive parameters, including epididymal sperm concentration, testicular tyrosine-phosphorylated protein expression, steroidogenic acute regulatory (StAR) protein expression, and caspase-3 and malondialdehyde levels, were examined. Results: The sperm concentrations ( × 10 6 /ml) of groups IV (58.75 ± 1.28) and V (55.93 ± 2.57) were improved significantly (p = 0.032) compared with that of group II (32.92 ± 2.14). The seminiferous epithelium in groups IV and V also increased, while caspase-3 expression decreased. In the melatonin-treated groups, the expression of tyrosine-phosphorylated proteins at 32 kDa was decreased and that of proteins at 47 kDa was increased compared with the MTX group. StAR protein expression was not altered in any of the groups. Conclusion: Our results indicate that melatonin improves the epididymal sperm concentration by decreasing the expression of caspase-3 and increasing that of tyrosine-phosphorylated proteins in MTX-treated testes.